Intramuscular and intratendinous placenta‐derived mesenchymal stromal‐like cell treatment of a chronic quadriceps tendon rupture. Issue 1 (5th January 2022) - Maleitzke, Tazio; Reinke, Petra; Agres, Alison N.; Alves, Sónia A.; Akyüz, Levent; Fleckenstein, Florian N.; Bichmann, Anna; Ofir, Racheli; Perka, Carsten; Duda, Georg N.; Winkler, Tobias
Abstract: Background: Quadriceps tendon ruptures (QTRs) are rare but debilitating injuries, often associated with chronic metabolic conditions or long‐term steroid treatment. While the surgical treatment for acute QTRs is described thoroughly, no common strategy exists for the often frustrating treatment of chronic, reoccurring QTRs. The pro‐angiogenic and immunomodulatory properties of placenta‐derived adherent mesenchymal stromal‐like (PLX‐PAD) cells have been described to protect musculoskeletal tissues from inflammation and catabolic cytokine migration, yet little is known about the regenerative potential of PLX‐PAD cells in repetitively damaged tendon tissue. Case: We report the case of an 80‐year‐old male patient with a chronic three‐time QTR of his right knee. The quadriceps tendon was reconstructed applying a conventional suture anchor repair procedure combined with a synthetic mesh augmentation and additional intramuscular and intratendineous PLX‐PAD cell injections as an individualized treatment approach. No adverse events were reported, and excellent radiological and functional outcomes with a passive range of motion of 0/0/120° knee extension‐flexion were observed at the 12 month follow‐up. Gait analysis confirmed restoration of joint motion, including gait speed, deficit in step length, and knee extensor muscle strength (pre‐surgery: 0.98 m/s, 40 cm, 42.4 ± 12.4 N; 9 months post‐surgery: 1.07 m/s, 0 cm, 10.4 ± 18.9 N) as well as hyperextension throughout stance and late swing phases (pre‐surgery: −11.2 ± 0.9°; 9 months post‐surgery: −2.7 ± 1.6°). Postoperative lymphocyte and cytokine analyses from the patient's peripheral blood serum suggested a systemic short‐term immunoregulatory reaction with postoperatively increased interleukin (IL)‐6 (pre‐surgery: 0.79 pg/mL; day 1: 139.97 pg/mL; day 5: 5.58 pg/mL; 9 months: 1.76 pg/mL) and IL‐10 (pre‐surgery: 0.9 pg/mL; day 1: 1.21 pg/ mL; day 5: 0.3 pg/mL; 9 months: 0.34 pg/mL) levels that decreased again over time. Conclusions: Herein, we demonstrate a successfully treated chronic QTR with a synergistic surgical and biological reconstructive treatment approach. This local add‐on treatment with PLX‐PAD cells may be considered in specific cases of chronic QTRs, not susceptible to traditional suture anchor procedures and which exhibit a high risk of treatment failure. Further scientific engagement is warranted to explore underlying immunomodulatory mechanisms of action behind PLX‐PAD cell treatment for tendon injuries.